2014
DOI: 10.1063/1.4890031
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optic response of polymer-stabilized blue phase liquid crystals

Abstract: The dynamic response of a polymer-stabilized blue phase liquid crystal (BPLC) is comprised of two distinct processes: Kerr effect-induced local reorientation and electrostriction-induced lattice distortion. A double exponential rise/decay model is proposed to analyze the underlying physical mechanisms. If the electric field is below a critical field (Ec), Kerr effect dominates and the response time is fast. However, when E > Ec electrostriction effect manifests, leading to an increased response time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…There are several solutions that have been identified to lower the operating voltage [4547] and make hysteresis free BPLC devices [39, 4851]. For example, modifications to the device structure have been proposed, such as the planar in plane switching (IPS) structure [52], interdigitated indium tin oxide (ITO) electrodes [53], the protrusion electrode structure [54], periodic corrugated electrodes [36], double-side in plane switching (DS-IPS) [44], and vertical field switching (VFS) [55].…”
Section: Introductionmentioning
confidence: 99%
“…There are several solutions that have been identified to lower the operating voltage [4547] and make hysteresis free BPLC devices [39, 4851]. For example, modifications to the device structure have been proposed, such as the planar in plane switching (IPS) structure [52], interdigitated indium tin oxide (ITO) electrodes [53], the protrusion electrode structure [54], periodic corrugated electrodes [36], double-side in plane switching (DS-IPS) [44], and vertical field switching (VFS) [55].…”
Section: Introductionmentioning
confidence: 99%
“…From previous study, it was found that the severity of electrostriction mainly depends on the soundness of polymer network. 31 Hence, by controlling the UV polarization axis with respect to the direction of the stripe electrodes of an IPS-BPLC cell, the formed anisotropic polymer network could result in anisotropic electrostriction correspondingly. In our experiments, we employed a large Δε nematic LC host JC-BP07N (JNC, Japan) whose physical properties are: Δn = 0.162 at λ = 633 nm, Δε = 302 at 100 Hz and 22°C, and T c = 87˚C.…”
Section: Methodsmentioning
confidence: 99%
“…The fitted time constants and the contribution of electrostriction effect, which is described by B/(A + B) in our model, are also included in Table 1. 31 All the values of t 1 lie in the submillisecond range while those of t 2 are around several milliseconds. These results correspond well with the previously reported response time of fast Kerr effect and the slow electrostriction effect.…”
Section: Dynamic Responsementioning
confidence: 97%
See 2 more Smart Citations